Evaluation of the safety profile of biological drugs used in the treatment of inflammatory bowel diseases - Moćko, Paweł (2017)
Introduction: Ulcerative colitis (UC) and Crohn disease (CD) are classified as nonspecific inflammatory bowel diseases (IBDs). The aim of the study was to compare the safety profile of biologic drugs in patients with IBDs.Methods: A systematic literature search was performed using PubMed, Embase, and CENTRAL. Randomized controlled trials comparing biologic drugs used in the treatment of patients with UC (infliximab, adalimumab, golimumab, and wedolizumab) or CD (infliximab, adalimumab, wedolizumab, certolizumab pegol, and ustekinumab) with placebo were analyzed. The safety profile of biologic drugs was assessed using a network meta-analysis (NMA). The NMA was performed separately for patients with UC and CD, and generally for patients with IBDs. The study was registered on PROSPERO (CRD42016032607, CRD42016032606, CRD42015029884).Results: For most comparisons and endpoints, the NMA showed no significant differences in the rate of adverse events. A significantly higher risk of injection site reaction was showed for adalimumab compared with placebo (patients with UC) and a significant advantage of certolizumab pegol over infliximab and placebo (patients with IBDs). Conclusion: There were no significant differences in the relative assessment of these drugs or in their safety profile, as compared with placebo.
Keywords: ulcerative colitis; biologic drugs; Crohn disease; network meta-analysis; safety profile